STUDENTS’ PERCEPTIONS ON THE USE OF BAHASA AND ENGLISH IN CLASSROOM: A CASE STUDY IN ONE SENIOR HIGH SCHOOL IN MEDAN - Risa Anggraini (Journal MELT (Medium for English Language Teaching), 2021)
This research was aimed to explore students’ perceptions on the use of language in EFL classroom. Researcher conducted this study in One Senior High School Medan. There were four twelfth graders participated in this study. Case study qualitative research was used in this study. Researcher collected the data through semi-structured interview and used interview protocol as the guideline. There were three major findings which categorized into themes such as 1) Students’ preferences on the use of Bahasa and English in EFL classroom, 2) Students’ perceptions on the language used in EFL classroom, and 3) Students’ expectations for the language choices in EFL classroom. From the findings, researcher found students’ perceptions on the use of language in classroom including their point of view and their expectations from their EFL teachers. Students prefered to use English fully, some wanted to use Bahasa because the lesson could be more comprehensible if the language used was in their own native language, and some expected that their EFL teachers could mix the language between Bahasa and English in the class.